High chrome cast iron for mineral processing and conveying equipment parts - A. S. Gudenko; N. S. Gushchin; E. A. Makarova; N. V. Parshikova (Литьë и металлургия, 2022)
The main reasons for the formation of microand macrocracks and other defects in waterjet castings, which significantly reduce their service life, are analyzed. It has been established that the introduction of ferroalloys together with the charge to the bottom of the arc furnace bath leads to a significant segregation of elements along the height (volume) of the melt in the bath furnace, and large primary chromium carbides remain in the casting structure. They, as a rule, form eutectics with austenite in the form of large conglomerates, which contribute to the appearance of microcracks in castings during their mechanical and thermal processing. It is shown that alloying, modification and homogenizing exposure of the melt for 5 min at 1550 °C and subsequent refining have a significant effect on the structure and morphology of the carbide phase and structural components of the metal base of high-chromium cast iron and purify it from harmful impurities and non-metallic inclusions. In addition, the amount of primary carbides is reduced, the formation of austenitic-carbide eutectic conglomerates is excluded, and the dispersion of the carbide phase and the structure of high-chromium cast iron are increased. Based on the ICH300Kh28NMWFTP cast iron created by JSC «NPO «TSNIITMASH», an effective export technology for the manufacture of waterjet castings has been developed, which makes it possible